EFFECT OF TRYPTOPHAN AND PH LEVEL ON INDOLE-3-ACETIC ACID (IAA) PRODUCTION BY Bacillus spp. - Jiraporn Inthasan; Chatprawee Dechjiraratthanasiri; Athipat Khamhung (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2026)
Tryptophan and pH are environmental factors that convincingly influence microbial growth, metabolism, and metabolite production. This study aimed to find out how tryptophan and pH affect the production of Indole-3-acetic acid (IAA) by Bacillus spp. in Nutrient Broth (NB) medium. A Completely Randomized Design (CRD) with six treatments and three replications was used. The confirmation bacterial strains were Brevibacillus agri, Brevibacillus borstelensis (2 isolates), and Bacillus subtilis. The NB medium was adjusted to four pH levels (5, 6, 7, and 8) and supplemented with different concentrations of tryptophan: 0, 102, 150, 300, 450, and 600 mg/ml. The results after incubated showed that Brevibacillus agri was detected the highest IAA content at pH level 7.0 with 600 mg/ml of tryptophan (204 µg/ml). Whereas Brevibacillus borstelensis and Bacillus subtilis caused the maximum of IAA contents at pH level 8.0 with 600 mg/ml of tryptophan at 79.31 µg/ml and 35.82 µg/ml respectively.